IMPLEMENTASI HADIS TENTANG AMR MA’RŪF DAN NAHI MUNKAR DALAM KITAB HADIS ARBA’ĪN SEBAGAI METODE PENCEGAHAN KENAKALAN ANAK SANTRI DI PONPES SAIFULLAH AN-NAHDLIYAH DESA BATU GEMUK KEC. NAMORAMBE - Sitompul, Muhammad Fachri; Muzakkir, Muzakkir (Jurnal Bilqolam Pendidikan Islam, 2024)
Islamic boarding schools are the most important resource in terms of religious education in Indonesia so that they have the potential to develop society. However, the reality often shows a different reality, although within the scope of Islamic boarding schools, where activities are more directed towards positive things, it cannot be denied that students can also be involved in delinquent activities in Islamic boarding schools. This study aims to implement the hadith nahi munkar in the book of hadith Arba'īn in an effort to prevent delinquency of students at the Saifullah An-Nahdliyah Islamic boarding school. This study uses a descriptive qualitative research method to explain and describe the object of study. The researcher used interview, observation, and documentation procedures to collect data in this study. The results of this study indicate that delinquency in the Saifullah An-Nahdliyah Islamic boarding school can be applied into three parts, namely mild delinquency; moderate delinquency; and severe delinquency. Furthermore, the hadith nahi munkar in the hadith book Arba'īn Nawawi when implemented in the Saifullah An-Nahdliyah Islamic boarding school environment in an effort to prevent students from getting acquainted with each other has a good impact on the boarding school. First, preventing by hand, the boarding school can make strict rules and policies through written rules. Second, preventing verbally, teachers and caregivers at the boarding school must provide a deep understanding to the students regarding the importance of avoiding evil. Third, preventing by heart, when the students see evil, they simply admit in their hearts that the act is an act that is prohibited in the boarding school environment. In these ways, students can maintain their faith and piety even though they cannot directly change the evil that exists around them.